2012
DOI: 10.1007/s00167-012-1896-7
|View full text |Cite
|
Sign up to set email alerts
|

Haemophilic knee arthropathy: long-term outcome after total knee replacement

Abstract: Purpose The objective of this study was to evaluate the long-term outcome and prosthetic survival of primary total knee arthroplasty in haemophilic patients. It was hypothesized that the infection and revision rate are higher and the outcome inferior when compared with patients without haemophilia. Methods Between 1985 and 2004, forty-three consecutive primary total knee replacements were performed in thirty haemophilic patients. These patients' charts were reviewed retrospectively. Twenty-five patients (34 kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
46
2
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 27 publications
5
46
2
2
Order By: Relevance
“…When looking at functional improvement postoperatively, many authors have suggested reasons more unique to the haemophilia population. Perception of better functional improvements can be attributed to the length of time the patient reports symptoms of arthropathy development before surgery, severity of symptoms, choice of implant, surgical technique, prolonged continuous infusions of factor replacement and early physical therapy .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When looking at functional improvement postoperatively, many authors have suggested reasons more unique to the haemophilia population. Perception of better functional improvements can be attributed to the length of time the patient reports symptoms of arthropathy development before surgery, severity of symptoms, choice of implant, surgical technique, prolonged continuous infusions of factor replacement and early physical therapy .…”
Section: Discussionmentioning
confidence: 99%
“…Articles that appeared to meet screening criteria were then cross‐examined using exclusion criteria: non‐English articles, use of cryoprecipitate or frozen blood plasma due to increased risk of co‐morbidities occurring post‐surgery and association with outdated surgical techniques, and studies reporting the outcomes of fewer than five knees. Studies reporting function based on the Western Ontario and McMaster University Arthritis Index (WOMAC) were excluded, based on the limited number of studies ( n = 2) using this instrument .…”
Section: Methodsmentioning
confidence: 99%
“…Several studies stated inferior outcomes regarding achievement of ROM in haemophilia patients. Even though TKA has been effective to get rid of flexion contractures, in some reports, total range of motion has not been reported to increase postoperatively . Contrariwise some reports like the ones performed by Viliani et al .…”
Section: Discussionmentioning
confidence: 97%
“…Most of the outcome measures including WOMAC questionnaire are subjective [44][45][46]. Most of the outcome measures including WOMAC questionnaire are subjective [44][45][46].…”
Section: Discussionmentioning
confidence: 99%